LncRNA LINC00588 Suppresses the Progression of Osteosarcoma by Acting as a ceRNA for miRNA-1972 - Zhou, Fu-Chao; Zhang, Yue-Hui; Liu, Hai-Tao; Song, Jia; Shao, Jiang (Frontiers in Pharmacology, 2020)
Increasing long-noncoding RNAs (lncRNAs) has been found to play an important role in the development of tumor. While, how its biological functions and underlying mechanism is still not very clear. In present study, we found that LINC00588 was downregulated in the OS in situ but upregulated in the metastatic tumor in the lung. Colony formation assay, CCK-8 assay, flow cytometry, would healing assay, transwell assay, RT-qPCR assay and the xenograft model experiment were conducted after overexpression and knockdown of the LINC00588 to investigate the influence of LINC00588 on cell proliferation, viability, apoptosis & cell cycle, migration, invasion, endothelial cell function, EMT(epithelial to mesenchymal transition) and tumor growth. The upregulated LINC00588 appeared to inhibit the cell proliferation, viability, migration, invasion, endothelial cell function, EMT, tumor growth but not apoptosis, and vice versa. Next we anticipated the LINC00588 bound to miRNA-1972 and significantly downregulated its expression via a software, and then been verified by the luciferase reporter assay. Next, inhibitor-miR1972, inhibitor negative control (NC), mimic-miR1972, mimic NC were respectively transfected into the OS cells. The downregulated of miRNA-1972 substantially inhibit the viability and invasion of osteosarcoma cells through CCK-8 assay, and transwell assay. The expression of TP53 were downregulated at protein level but not m-RNA level after overexpressed the miRNA-1972. Taken together, the LINC00588 work in the OS development by downregulating the expression of miRNA-1972, which could inhibited the expression of TP53. Hence, we believed that LINC00588/miRNA-1072/TP53 axis could potentially serve as therapeutic targets or diagnostic biomarkers for osteosarcoma.